A GIS model for personal exposure to PM10 for Dublin commuters - PILLA, FRANCESCO (Trinity College Dublin, 2012)
The project has focused on a number of scientific issues in the development of the GIS air quality model for the Dublin Area and its Satellite Towns . Firstly, how to model air quality by integrating existing and self - implemented air quality models and a Geographical Information System platform . Secondly, how to generate input data for the models to allow the estimation of air quality at any location in the Dublin Area . These issues have been addressed by implementing various tools: a method to calculate the background concentration levels, a method to model the dispersion of pollutants from road traffic in urban street canyons , a method to model the dispersion of pollutants from road traffic in general conditions , and a method to calculate the dispersion of pollutants from point and area sources . Thirdly, an approach to include all the models above into GIS tools has been discussed. Fourthly, an approach for disseminating results from air quality studies has been described and proposed.
PUBLISHED
Keywords: GIS; Smart & Sustainable Planet; ARTIFICIAL NEURAL NETWORKS; Air quality modelling; Environmental Impacts of Transport; Environmental engineering; Environmental systems modelling; GEOGRAPHIC INFORMATION SYSTEM (GIS); STOCHASTIC MODELLING; Spatial Modelling